HUBUNGAN ANTARA KUALITAS KEHIDUPAN SEKOLAH DENGAN KEDISIPLINAN SISWA KELAS BERPINDAH PADA KELAS XII SMAN 3 SEMARANG - Febriani, Nada; Widodo, Prasetyo Budi; Kristiana, Ika Febrian (Jurnal Psikologi, 2013)
Purpose of this study was to determine the relationship between quality of school life with student's discipline of moving class at students class XII SMAN 3 Semarang. Quality of school life is students perception about dimensional of school, including student perspective towards their school, the connection with teachers, feeling that student will achieve success in school, the student chance to face future, social integration, and exlporing. Student's discipline is the meaning of their willingness to obey all regulation in their school. The subject of this study was 301 students of moving class at students class XII SMAN 3 Semarang. Cluster random sampling is used. Technique of data collection used the discipline scale (30 aitem valid Î±=0,915) and the scale of quality of school life (31 aitem valid Î±=0,925). Based on the analysis of simple regression showed rxy = 0.520 with p=0.000 (p<0.05). This results indicate that the proposed hypothesis, the existance of a relationship between quality of school life with student's discipline of moving class. Positive coefficient correlation value indicate more positive quality of school life, the higher discipline, and vice versa. Effective quality of school life contributes 27.1% on discipline and 72.9 % were influenced by others.Keywords: Student's Discipline, quality of school life, moving class